Technology Change = Gender Change? Androcentric Construction of Engineering as Symbolic Resource in the German-Speaking Area of Renewable Energies. Issue 1 (2nd January 2017) - Prietl, Bianca
ABSTRACT: This paper is concerned with how engineers working in renewable energies in Germany and Austria position themselves and their professional activity within this relatively new field of engineering occupation by mobilizing a specific androcentric construction of engineering as a symbolic resource. Drawing on qualitative interviews, the argument unfolds in three steps: First, the paper reconstructs how engineers draft an image of their professional activity by symbolically aligning it with established understandings of engineering in traditional areas of engineering occupation and by simultaneously distancing it from allegedly 'other' notions of engineering practice that are framed as 'alternative'. The discursive distinction between professional engineering and its alleged 'alternative' counterpart constitutes the former as hard, sincere, structured, and reliable activity based on an instrumental rationality. Second, it is shown how the professional/alternative distinction is gendered with 'the alternative' being devaluated and feminized. Consequently, it is argued that there is an implicit association between the discursively constituted idea of professional engineering and masculinity. Third, this discursive construction of engineering is interpreted as a symbolic resource in the engineers' claim to be recognized as professional actors within renewable energies and, thus, in their struggle for favourable positions within this social field of power.